2000
DOI: 10.1099/0022-1317-81-10-2545
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Spodoptera exigua baculovirus recombinant with a 10·6 kbp genome deletion that retains biological activity

Abstract: When Spodoptera exigua multicapsid nucleopolyhedrovirus (SeMNPV) is grown in insect cell culture, defective viruses are generated. These viruses lack about 25 kbp of sequence information and are no longer infectious for insects. This makes the engineering of SeMNPV for improved insecticidal activity or as expression vectors difficult to achieve. Recombinants of Autographa californica MNPV have been generated in insects after lipofection with viral DNA and a transfer vector into the haemocoel. In the present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 45 publications
0
41
0
1
Order By: Relevance
“…required for virus replication in cultured insect cells or in vivo after intrahaemocoelic injection. In previous studies involving SeMNPV deletion mutants generated via cell culture or in vivo (Heldens et al, 1996;Dai et al, 2000), it could never be excluded that a minor amount of intact helper virus was still present enabling predominant replication of deletion mutants. With the current strategy using bacmids, pure baculovirus mutants were generated from single-copy bacterial artificial chromosomes maintained in E. coli (Luckow et al, 1993;Pijlman et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…required for virus replication in cultured insect cells or in vivo after intrahaemocoelic injection. In previous studies involving SeMNPV deletion mutants generated via cell culture or in vivo (Heldens et al, 1996;Dai et al, 2000), it could never be excluded that a minor amount of intact helper virus was still present enabling predominant replication of deletion mutants. With the current strategy using bacmids, pure baculovirus mutants were generated from single-copy bacterial artificial chromosomes maintained in E. coli (Luckow et al, 1993;Pijlman et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…These mutants, with deletions up to 25 kb, often lack the ability to infect S. exigua larvae by oral ingestion of OBs (Heldens et al, 1996). Therefore, the genetic engineering of SeMNPV via recombination in cell culture is complicated (Dai et al, 2000) and precludes the in vitro production of biologically active SeMNPV in insect cell bioreactors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of such deletion mutants is therefore likely to be deleterious to the fitness of a virus population in vivo, although deletion mutants that can increase fitness are found in some natural baculovirus isolates (Ló pez-Ferber et al, 2003). Dai et al (2000) found that alternate passaging of baculoviruses in insect cells and larvae resulted in sustained infectivity for insect larvae, suggesting that purifying selection (Li, 1997) occurs in these animals. In other words, there may be stabilizing selection for a particular trait, in this case the ability to replicate autonomously.…”
mentioning
confidence: 99%